Best Practice Guidelines for Assessment and Management of Osteoporosis in Adult Patients Undergoing Elective Spinal Reconstruction. Issue 2 (15th January 2022) - Sardar, Zeeshan M.; Coury, Josephine R.; Cerpa, Meghan; DeWald, Christopher J.; Ames, Christopher P.; Shuhart, Christopher; Watkins, Colleen; Polly, David W.; Dirschl, Douglas R.; Klineberg, Eric O.; Dimar, John R.; Krohn, Kelly D.; et al.
Abstract : Study Design: Expert consensus study. Objective: This expert panel was created to establish best practice guidelines to identify and treat patients with poor bone health prior to elective spinal reconstruction. Summary of Background Data: Currently, no guidelines exist for the management of osteoporosis and osteopenia in patients undergoing spinal reconstructive surgery. Untreated osteoporosis in spine reconstruction surgery is associated with higher complications and worse outcomes. Methods: A multidisciplinary panel with 18 experts was assembled including orthopedic and neurological surgeons, endocrinologists, and rheumatologists. Surveys and discussions regarding the current literature were held according to Delphi method until a final set of guidelines was created with over 70% consensus. Results: Panelists agreed that bone health should be considered in every patient prior to elective spinal reconstruction. All patients above 65 and those under 65 with particular risk factors (chronic glucocorticoid use, high fracture risk or previous fracture, limited mobility, and eight other key factors) should have a formal bone health evaluation prior to undergoing surgery. DXA scans of the hip are preferable due to their wide availability. Opportunistic CT Hounsfield Units of the vertebrae can be useful in identifying poor bone health. In the absence of contraindications, anabolic agents are considered first line therapy due to their bone building properties as compared with antiresorptive medications. Medications should be administered preoperatively for at least 2 months and postoperatively for minimum 8 months. Conclusion: Based on the consensus of a multidisciplinary panel of experts, we propose best practice guidelines for assessment and treatment of poor bone health prior to elective spinal reconstructive surgery. Patients above age 65 and those with particular risk factors under 65 should undergo formal bone health evaluation. We also established guidelines on perioperative optimization, utility of various diagnostic modalities, and the optimal medical management of bone health in this population. Level of Evidence: 5 Abstract : Supplemental Digital Content is available in the textCurrently, no guidelines exist for the management of osteoporosis and osteopenia in patients undergoing spinal reconstructive surgery. This expert panel was created to establish best practice guidelines that could identify and treat patients with poor bone health prior to undergoing elective spinal reconstruction.